Pametna kartica - Jurišić, Aleksandar (Uporabna informatika (Ljubljana), 1997)
Smart cards provide the degree of security necessary to make computer networking truly viable. They unify telecommunications and computing. After a brief historical overwiew of the development of cards, we survey three basic tipes of memory cards, in order to better understand the advantages of smart cards. The security aspects of smart cards are illustrated by two examples. Applications of smart cards are surveyed and a wiev for their future possibilities are given.
Keywords: elektronsko poslovanje; informatika; kriptografija; pametne kartice; računalništvo; varnost; zaščita